Analisis Leader Member Exchange Pada Bisnis Keluarga - Putri Hanifah, Ajeng; Bambang Hermanto; Pratami Wulan Tresna (Bahtera Inovasi, 2022)
In building leadership skills, one of the things that is needed is how to establish a leader relationship with employees so that they can produce better performance in the business. Leader Member Exchange (LMX) theory argues that the most effective leadership process arises when leaders and employees cultivate mature, high-quality relationships, not only on the job but also soial-emotional. This research was conducted using qualitative methods to find out how the quality of the relationship between leaders and employees in the family business, Family Handicraft in Tasikmalaya. Conducted through semi-structured interviews to find out in depth and explore the condition of leadership. The results revealed that the leadership conditions in the Family Handicraft family business are of high quality resulting in good business performance amid the Covid-19 Pandemic conditions, characterized by high production demand for exports to Japan in 2021. Keywords : leadership; leader member exchange; family business